Efektivitas Pembelajaran Bahasa Jepang Melalui Video Singkat (YouTube Shorts, TikTok, dan Reels) - Cynthia Octavania Putri Salma; Icha Maulidya; Adli Farizi; Glorian Hilarius Kiantin Beda; Humannisa Rubina Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The rapid development of social media has changed the learning patterns of the digital generation, including in learning Japanese. This study examines the effectiveness of short videos based on social media such as YouTube Shorts, TikTok, and Instagram Reels as a medium for learning Japanese. The study used a quantitative approach through a descriptive survey with a Likert scale instrument, involving 61 respondents who had experience teaching Japanese using short videos. The findings showed that this media effectively improved vocabulary and phrase understanding, practised pronunciation, and built learning motivation. However, its effectiveness in developing productive skills such as speaking and writing is still limited. Most respondents also stated the need for longer content to deepen mastery of the material. These findings indicate that short videos have the potential to be an interesting, practical, and easily accessible learning medium. However, the development of learning content should be directed at combining the visual appeal of short videos and communication practice-oriented materials to achieve more optimal and sustainable learning outcomes.